2000
DOI: 10.1046/j.1365-2109.2000.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of cholesterol oxidation products in commercial fish meals and their formation during storage

Abstract: Twenty-two samples of commercial ®sh meals from Norway, Chile and Peru were analysed for cholesterol and oxysterols using gas chromatography. Cholesterol content ranged from 25.2 to 64.8 g kg ±1 total lipids. Detectable levels of the oxysterols 7b-hydroxycholesterol and 7-ketocholesterol were found and their identity was con®rmed by gas chromatography-mass spectrometry. Samples of ®sh meal exhibited wide variability in oxysterols content, 7b-hydroxycholesterol ranging from 3.9 to 105.6 mg kg ±1 total lipids (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2001
2001
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
4
8
0
Order By: Relevance
“…Oxysterols formation was studied in a sample of Norse LT94 fish meal stored on a laboratory shelf: both 7β‐hydroxycholesterol and 7‐ketocholesterol increased by up to about 350% of their initial content at 42 days of storage, and then decreased. To our knowledge, these results by Scolari et al . (2000) demonstrated for the first time the occurrence of cholesterol oxidation products in fish meal.…”
Section: Application To Fish Meal and Aquafeedsmentioning
confidence: 58%
“…Oxysterols formation was studied in a sample of Norse LT94 fish meal stored on a laboratory shelf: both 7β‐hydroxycholesterol and 7‐ketocholesterol increased by up to about 350% of their initial content at 42 days of storage, and then decreased. To our knowledge, these results by Scolari et al . (2000) demonstrated for the first time the occurrence of cholesterol oxidation products in fish meal.…”
Section: Application To Fish Meal and Aquafeedsmentioning
confidence: 58%
“…20% was extracted with the oil (9). A recent study reported COP levels in 22 samples of commercial fish meals from several countries (11). It was demonstrated that the contents of 7β-hydroxycholesterol and 7-ketocholesterol ranged from 0.4 to 9.4 µg/g and 0.2 to 5.0 µg/g, respectively, in these fish meal samples.…”
Section: Resultsmentioning
confidence: 92%
“…The level of 7β-hydroxycholesterol and 7-ketocholesterol ranged from 0.4 to 9.4 µg/g and from 0.2 to 5.0 µg/g fish meal, respectively, in 22 samples of commercial fish meals from several countries (11). The authors pointed out that as a result of difficulties in determining PV, the COP content is the more accurate figure to use for describing the oxidative status of fish meal and fish feeds.…”
mentioning
confidence: 99%
“…The presence of COPs in samples of commercial fish meals from Norway, Chile, and Peru stored at −20 °C for up to 56 d was analyzed (Scolari and others ). The authors tested for 7β‐hydroxycholesterol, 19‐hydroxycholesterol, 20α‐hydroxycholesterol, 25‐hydroxycholesterol, 5,6α‐epoxycholesterol, cholestanetriol, and 7‐ketocholesterol, but only detected 7β‐hydroxycholesterol and 7‐ketocholesterol in the evaluated samples.…”
Section: The Main Factors That Influence the Formation Of Cops In Fishmentioning
confidence: 99%